Teaching Agricultural Biotechnology with Animation to Enhance Students Visual Literacy and Food Security Understanding - Trista Niswa Fadliya; Fidia Fibriana (Jurnal Pijar MIPA, 2026)
Food security is a global strategic issue that requires science and technology-based innovations, one of which is plant tissue culture biotechnology. However, tissue culture is abstract and difficult for students to understand because it involves microscopic processes that cannot be directly observed. Therefore, instructional media that can visually illustrate these concepts are needed. This study aimed to develop an animated video on plant tissue culture, based on visual literacy principles and to evaluate its feasibility and effectiveness in biotechnology learning related to food security. This research employed a Research and Development (R&D) approach, using a modified 4D model through the development stage. The trial was conducted with 20 ninth-grade junior high school students who had not previously used animated video media in tissue culture learning and were willing to participate in the entire sequence of learning activities, using a one-group pretest-posttest design. Research instruments included expert validation sheets, student response questionnaires, and pretest and posttest assessments. Data were analyzed using descriptive and inferential statistics, including the Wilcoxon Signed Rank Test and N-gain analysis. The study results showed that the developed media was highly feasible, with an overall validation score of 98.89% from six validators, all of whom were media and material experts, who categorized it as "very feasible." Student responses were also very positive, with 81.2% in favor. Effectiveness analysis showed a significant improvement from pretest to posttest scores (p < 0.001), with an N-gain of 0.7722 (high category), indicating that the media effectively enhanced students’ conceptual understanding of plant tissue culture. The novelty of this study lies in integrating visual literacy indicators and the food security context, and utilizing Artificial Intelligence technology to develop educational animation. These findings suggest that AI-based animated media can concretize complex biotechnology concepts and improve the quality of science learning.